2017
DOI: 10.1007/s00330-017-5036-0
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and clinical value of CT-guided 125I brachytherapy for metastatic soft tissue sarcoma after first-line chemotherapy failure

Abstract: • I brachytherapy is feasible and valuable for treating metastatic soft tissue sarcoma. • I brachytherapy represents a prominent activity in disease control. • I brachytherapy can achieve better symptom relief and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 25 publications
4
20
0
Order By: Relevance
“…Previous studies have shown that the maximum diameter is an independent factor affecting the LTPFS of 125 I brachytherapy [21]. The same conclusion was obtained in this study.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Previous studies have shown that the maximum diameter is an independent factor affecting the LTPFS of 125 I brachytherapy [21]. The same conclusion was obtained in this study.…”
Section: Discussionsupporting
confidence: 92%
“…One of the main advantages of 125 I brachytherapy is the high local control [16,21,[35][36][37]. Therefore, we used LTPFS as the primary end point, and used Kaplan-Meier analysis and log-rank test to explore the factors affecting LTPFS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to expand the indications of RSI-BT, CT-guidance technique was integrated into RSI-BT in 2002 in China, which was used to treat head and neck, thoracic, abdomen, and spinal vertebrate carcinoma [25][26][27][28][29][30]. The CTguided 125I RSI-BT was very safety and effective approach for anti-cancer treatment, especially for recurrent or metastasis carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…In order to expand the indications of RSI-BT, CT-guidance technique was integrated into RSI-BT in 2002 in China, which was used to treat head and neck, thoracic, abdomen, and spinal vertebrate carcinoma [25][26][27][28][29][30]. The CT-guided 125I RSI-BT was very safety and effective approach for anti-cancer treatment, especially for recurrent or metastasis carcinomas.…”
Section: Discussionmentioning
confidence: 99%